Understand the Potential Role of Aureobasidium pullulans, a Resident Microorganism From Grapevine, to Prevent the Infection Caused by Diplodia seriata - Pinto, Cátia; Custódio, Valéria; Nunes, Mariana; Songy, Aurélie; Rabenoelina, Fanja; Courteaux, Barbara; Clément, Christophe; Gomes, Ana Catarina; Fontaine, Florence (Frontiers in Microbiology, 2018)
Grapevine trunk diseases (GTDs) are one of the major concern amongst grapevine diseases, responsible for the decline of vineyards and for several economical losses. Since grapevine is naturally colonized by resident microorganisms such as Aureobasidium pullulans, the present challenge is to understand their biocontrol potential and how such microorganisms can be successfully integrated in the control of GTDs. In this context, the first priority consists to exploit the plant-beneficial-phytopathogen interactions in plant model systems, to identify the most prevalent equilibrium limiting expression of GTDs expression. In the current study, we deep characterized the biocontrol potentialinteraction of a resident and abundant microorganism from grapevine - Aureobasidium pullulans strain Fito_F278 - against D. seriata F98.1, a Botryosphaeria dieback agent, and analyzed its interaction with plant (cv Chardonnay). Results revealed that A. pullulans strain Fito_F278 was able to reduce significantly the mycelium growth of D. seriata F98.1 at 33.41 ± 0.55%, under in vitro conditions, though this reduction is possibly dependent on a direct interaction between strain Fito_F278 and pathogen. in vitro conditions. In addition, it was demonstrated that the relative frequency of D. seriata in grapevine was prominently reduced from 25% in the presence of strain Fito_F278. Furthermore, strain Fito_F278 conferred plant protection not only through an antagonistic interaction but also by promotingwas able to promote an induction of some plant defense responses in cutting plants, one week after the D. seriata F98.1 phytopathogen infection. Results also evidenced that strain Fito_F278 colonized efficiently grapevine at both epiphyte and endophyte level, and could persist on plant roots for long-periods (up to two months after its inoculation) and grow at different pH and high salinity conditions. Moreover, a significant decrease of the microbial load from soil and rhizosphere was observed in plants treated with the strain Fito_F278, suggesting its competitivity potential in a microbial ecosystem. Altogether, the present study gives the first insights about the interaction of A. pullulans strain Fito_F278, a resident microorganism, with grapevine,; its natural biocontrol potential role against a Botryosphaeria dieback agent,; and highlights its importance to towards more resilient grapevine.